Fixed point theorems of modified Mann and Ishikawa iterations. Issue 5 (4th July 2021) - Malih, Sabah Hassan
Abstract: In this paper, we prove fixed point results of asymptotically nonexpansive mappings in uniformly convex Banach spaces under Fibonacci-Mann and Ishikawa iterations also prove some results weak convergence theorems with Opial condition.